vulnerability of islamic banking - hasan albanna (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2017)
The recent global financial crisis has renewed the focus on the resistance of Islamic banks in order to confront the crisis. While several empirical studies show that Islamic banks have no resist from the crisis. thus, Islamic banks run their business side by side with their counterpart and play the game under the same umbrella and the rules of game. In case of Indonesia, which implement dual banking system, Islamic banks have potential to be effected by the variables of conventional banks. Which mean, this condition led the Islamic banks have the vulnerable spot in economic life. This paper aim to examine the stability of Islamic banks and to discern dynamic behavior of Islamic banks to the macroeconomic variables such as GDP, inflation rate, exchange rate and interest rate. the measure of stability of Islamic banks formulated as z-score. Then, We use VAR/VECM analysis in order to see the dynamic behavior and the vulnerability of Islamic banks. the paper found several findings, first, during the global financial crisis, Islamic banks more stable than the conventional banks, while after the global financial crisis conventional banks tend to be more stable than Islamic banks. Second, From the IRF test display that Islamic banks react sensitively to the shock of interest rate. however, Islamic banks prohibit the practice of interest rate. even though, in practical reason, Islamic bank use interest rate as benchmarking to determine the price. This condition put the Islamic Banks in vulnerable condition. Third, the FEVD test showed that the stability of Islamic banks mostly contribute by its own stability then followed by GDP, interest rate, exchange rate and Inflation. At the seventh period the stability of Islamic banks mostly contribute by its stability then followed by Inflation rate, GDP, exchange rate and interest rate.